Cognizione logica e modelli mentali - Alberto Binazzi (Firenze University Press, 2012)
The aim of this paper is to investigate mental model theory, introduced by Philip Johnson-Laird to describe a ground level of logical cognition, concerning propositional logic and the fragment of predicate logic covering syllogisms. In order to appreciate the philosophical implications of the theory, the nature of mental models and the resulting picture of human rationality are discussed, by considering recent developments of the theory as well. We examine the issues concerning deductive competence and its computational implementation and argue that the notion of mental model calls for embodied cognitive architecture out of which 'reasoners' can construct models. Finally, we highlight the need of updating the concept of mental model through embodied cognition, with reference to spatial and perceptual abilities in reasoning.